2017
DOI: 10.1021/acs.orglett.7b02480
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dihydropyrazoles via Ligand-Free Pd-Catalyzed Alkene Aminoarylation of Unsaturated Hydrazones with Diaryliodonium Salts

Abstract: A ligand-free, palladium-catalyzed aminoarylation reaction of the unactivated alkenes in β,γ-unsaturated hydrazones is described. This protocol enables efficient and simultaneous formation of C(sp)-N and C(sp)-C(sp) bonds under mild conditions, providing a practical and general approach to various diversely substituted dihydropyrazoles in generally good yields, without the use of any stoichiometric external oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…On the basis of our recently reported Pd-catalyzed aminoarylation, we examined the feasibility of the target alkene aminoaroylation of β,γ-unsaturated hydrazone 1a with diphenyliodonium tetrafluoroborate 2a under 1 atm of CO at room temperature. Gratifyingly, using the combination of Pd­(TFA) 2 (10 mol %) and PPh 3 (20 mol %) as the catalyst in the presence of i PrNEt as a base, the desired reaction indeed worked to give the aminoaroylation product 3aa in 48% yield (Table , entry 1).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…On the basis of our recently reported Pd-catalyzed aminoarylation, we examined the feasibility of the target alkene aminoaroylation of β,γ-unsaturated hydrazone 1a with diphenyliodonium tetrafluoroborate 2a under 1 atm of CO at room temperature. Gratifyingly, using the combination of Pd­(TFA) 2 (10 mol %) and PPh 3 (20 mol %) as the catalyst in the presence of i PrNEt as a base, the desired reaction indeed worked to give the aminoaroylation product 3aa in 48% yield (Table , entry 1).…”
mentioning
confidence: 90%
“…For example, the groups of Muniz and Sorensen independently disclosed the first Pd-catalyzed oxidative diamination of sulfonamides and aminoacetoxylation of N -tosyl carbamates, respectively; in these processes, PhI­(OAc) 2 serves as an oxidant or as both an oxidant and a source of acetate (Scheme a). Inspired by these pioneering works and the inherent properties of diaryliodonium salts, we have also recently developed a general and mild Pd­(TFA) 2 -catalyzed aminoarylation reaction of β,γ-unsaturated hydrazones using diaryliodonium salts, leading to a practical access to diversely substituted dihydropyrazoles (Scheme b) . Mechanistically, we postulate that the overall sequence to be aminopalladation and metal oxidation, followed by aryl-nitrogen bond formation from the Pd IV intermediate; diaryliodonium salts work as external oxidants and aryl sources.…”
mentioning
confidence: 99%
“…The synthesis of pyrazoline derivatives has gained considerable attention from the synthetic community, because of their remarkable biological activity and widespread natural occurrence, as well as versatile utility as synthetic intermediates in organic synthesis . Among the great deal of effort toward efficient syntheses of functionalized pyrazolines from diverse precursors, , the direct cyclization/difunctionalization of β,γ-unsaturated hydrazones with a functional group reagent source is an attractive method, because of the easy availability of the substrates and the simultaneous setup of a second valuable functional group. For instance, Han, Loh, and Sodeoka et al found that in the presence of oxidants, β,γ-unsaturated hydrazones could give a hydrazonyl radical intermediate I . Intermediate I then undergoes fast 5-exo-trig cyclization to yield the corresponding C-centered radical II , which could be trapped by radical acceptors to produce functionalized pyrazolines (reaction 1a in Scheme ).…”
mentioning
confidence: 72%
“…6 Furthermore, a palladium catalyst was also applied by Xiao and Chen to the aminoarylation of unsaturated hydrazones, in which the alkylpalladium complex V is a key intermediate (reaction 3 in Scheme 1). 7 Although impressive progress has been made in recent years, given the fact that, in most cases, the biological profile of pyrazolines is dependent on their substitution patterns and structural diversity, the research is far from exhaustive and much remains to be explored. In particular, the introduction of many useful functional groups, such as azide group, halogen group, and thionitrile group to the pyrazoline core is still a challenge.…”
mentioning
confidence: 99%
“…In 2017, Xiao and Chen established an efficient ligand-free Pd(II)-catalyzed aminoarylation of β,γ-and γ,δ-unsaturated hydrazones 85 using diary-liodonium salt 86 as the aryl source and terminal oxidant (Scheme 15). [36] This method was characterized by good functional group compatibility, convenient materials, and mild reaction conditions. Remarkably, the method provides a practical and general method for the preparation of a variety of different substituted dihydropyrazoles and tetrahydropyridazines with moderate yields and does not require the stoichiometric use of an external oxidant.…”
Section: Palladium-catalyzed Cyclizationmentioning
confidence: 99%